Dissent and disparagement: Dealing with conflict and the pain of rejection in John - Loader, William R. G. (HTS teologiese studies, 2021)
This article addressed the issue of how the author of the Gospel according to John portrayed dissent, in particular, how the author had his protagonists respond to the experience of rejection by those typically designated as ‘the Jews’. Research thus far has usually focused on the identity of the dissenters but rarely on the way dissent was handled. This article’s aim was to examine the range of responses to dissent. It employed a sequential reading of the text to identify the various responses and then brought these findings into comparison with the way dissent was handled in related documents of the time, Matthew and Hebrews. It found that responses included not only argument and blame, including threat of divine wrath but also, beyond these, ad hominem allegations that those who dissent were inherently bad or beholden to the devil or had not been predestined or chosen by God to respond. Such categories were, however, not absolute, because the author assumed that people could choose to respond positively and so move from one apparently fixed and predetermined category to another. They served a rhetorical function. A further ploy was to reduce Israel’s tradition to witness and foreshadowing within the tension of asserting both continuity and discontinuity.Contribution: The article concluded that such strategies served in part to comfort and reassure hearers engaged in the process of grief at rejection. As such they warranted critical reflection.